Chemical constituents from the branches and leaves of Alchornea annamica. Issue 9 (3rd May 2022) - Phan, Nguyen Huu Toan; Thuan, Nguyen Thi Dieu; Hien, Nguyen Thi Thu; Huyen, Pham Van; Hanh, Tran Thi Hong; Quang, Tran Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai
Abstract: Phytochemical investigation of the branches and leaves of Alchornea annamica led to isolation of ten secondary metabolites, including two new megastigmane glucosides alnamicosides A (1 ) and B (2 ). The structure elucidation was confirmed by 1 D and 2 D NMR, ECD as well as HR-QTOF-MS experiments. The megastigmane derivatives 1  − 3 exhibited inhibitory effects on LPS-induced NO production in RAW264.7 cells with IC50 values of 78.72 ± 1.90, 77.40 ± 9.40 and 82.16 ± 4.56 µM, respectively. This is the first report on chemical constituents and biological activity of the plant A. annamica . Graphical Abstract: